A template-directed synthesis of metal–organic framework (MOF-74) ultrathin nanosheets for oxygen reduction electrocatalysis. Issue 16 (2nd March 2021) - Fan, Rui; Kang, Ning; Li, Yuzhen; Gao, Lizhen
Abstract : Layered double hydroxide (LDH) is employed as a layered template to synthesize ultrathin Ni-MOF-74 nanosheets. The two-dimensional structure brings numerous exposed unsaturated active sites and enhanced conductivity for Ni-MOF-74. Abstract : Metal–organic frameworks (MOFs) have received wide attention for their promising applications in numerous fields due to their tailorable structure, metal centers and porosity. However, the low mass permeability, poor conductivity and blockage of active metal centers severely restrict the utilization of MOF systems in electrocatalysis. Two-dimensionalization can endow MOF materials extra unsaturated metal centers and enhanced electron-transfer ability, and could be an effective strategy to achieve high-performance MOF-based electrocatalysts. Herein, Ni-MOF-74 nanosheets are synthesized using layered double hydroxide (LDH) as a template to directly grow ultrathin structures. Benefiting from the two-dimensional structure, Ni-MOF-74 nanosheets with carbon substrate exhibit an enhanced ORR electrocatalytic property with positive half-wave potential (+0.83 V vs. RHE), a large current density (3.9 mA cm −2 ), four-electron selectivity and a promising long-term durability.